Effectiveness of iron therapy on breath holding spells in the children - bidabadi, Elham; Poornabi Darzi, Sedigheh; Mashouf, Parham; Shahraki, Tamkin (Iranian Journal of Child Neurology, 2019)
The pathophysiology and mechanism of Breath-Holding Spells (BHS) remain controversial, and the relationship between BHS and anemia has not been clarified, although iron supplementation appears to be effective in many patients. We aimed to assess the probable relation of iron level with initiation of these spells in children. Materials & Methods Overall, 42 children with a diagnosis of BHS, aged between 6 months to 2 yr were enrolled during Mar 2015 to Dec 2016 at Rasht 17th Shahrivar Hospital, Rasht, northern Iran. Ferrous sulfate solution prescribed 6 mg/kg/d, 3 times daily, for all of cases, regardless of their iron levels, and the response to the treatment was evaluated. Results Twenty-five patients were boys (59.52%). The mean age for all patients was 11.71±4.63 months. Positive family history detected in 33.33%; iron deficiency anemia in 21.42%, depletion of iron stores in 52.38%, and normal iron status in 26.19% of cases. Simple spells showed significantly higher mean of Hb in comparison with severe spells (P=0.008); also increased number of spells per month significantly decreased the mean of Hb (P=0.007). Mean frequency of spells was 40.14±47.08 before and 11.14±31.10 after iron therapy, per month (P<0.0001). Overall, 32 patients (76.19%) had complete control of spells, 7 patients (16.66%) partial, 2 cases (4.76%) weak, and 1 child (2.38%) no response after iron therapy. Conclusion Iron deficiency anemia may have an important role in BHS, and treatment of anemia may decrease number of the spells.